EFEKTIVITAS STRATEGI REACT UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI GETARAN, GELOMBANG DAN BUNYI KELAS VIII-1 SMP NEGERI 4 MEDAN TAHUN AJARAN 2019/2020 - Juriah Siregar (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
With details, there were no students (0%) who got very low scores (0-20), students who got low scores (21-40) were found as many as 3 students (10%), students got moderate scores (41-60) as many as 13 students (39%), got high scores (61-80) as many as 16 students (51%) and there were no students who got very high scores (81-100). Of the 32 students in the second cycle, 94% were declared complete, while 2 students had not experienced completeness, 6% with an average score of 87.33. Students are expected to be more active in the learning process in order to obtain better learning outcomes.